2019
DOI: 10.1080/01425692.2019.1665498
|View full text |Cite
|
Sign up to set email alerts
|

Socialisation and citizenship preparation in vocational education: Pedagogic codes and democratic rights in VET-subjects

Abstract: Previous studies of citizenship preparation in upper secondary school, including studies on vocational programmes, have primarily focused on general subjects. Potential and actual roles of vocational subjects in this context have received little attention, so we have little knowledge of what is likely a significant part of the citizenship preparation that occurs in vocational programmes. Drawing on the work of Basil Bernstein and ethnographic data, this study presents an analysis of socialisation processes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In addition, the work of Swedish researchers Nylund, Rosvall, Ledman and Rönnlund has been crucial in facilitating a better understanding of the Bernsteinian concepts through their applications of these ideas in contexts that are familiar to me. Their work also showcase how the analytical concepts and perspective chosen for this thesis are relevant to studies within the Swedish educational context (Ledman, Rosvall, & Nylund, 2018;Nylund, 2013;Nylund, Ledman, Rosvall, & Rönnlund, 2020;Nylund & Rosvall, 2016Nylund et al, 2018;Nylund et al, 2017;Rönnlund et al, 2019). Additionally, the argument made by Singh, Thomas, and Harris (2013), that the Bernsteinian analytical concepts contribute to critical education policy analyses, reassured me that the framework could be used in a study of policy as well as of practice.…”
Section: Discussion About and Additions To The Frameworkmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, the work of Swedish researchers Nylund, Rosvall, Ledman and Rönnlund has been crucial in facilitating a better understanding of the Bernsteinian concepts through their applications of these ideas in contexts that are familiar to me. Their work also showcase how the analytical concepts and perspective chosen for this thesis are relevant to studies within the Swedish educational context (Ledman, Rosvall, & Nylund, 2018;Nylund, 2013;Nylund, Ledman, Rosvall, & Rönnlund, 2020;Nylund & Rosvall, 2016Nylund et al, 2018;Nylund et al, 2017;Rönnlund et al, 2019). Additionally, the argument made by Singh, Thomas, and Harris (2013), that the Bernsteinian analytical concepts contribute to critical education policy analyses, reassured me that the framework could be used in a study of policy as well as of practice.…”
Section: Discussion About and Additions To The Frameworkmentioning
confidence: 90%
“…The consequences for students when employers have the power to shape the training of their own workers, as they do in HVE, are twofold. Firstly, because the training is formed to meet employers' production needs, the curricula overlook knowledge that enables autonomous reflection and critical thinking (Nylund et al, 2020;Nylund & Rosvall, 2016;Rönnlund et al, 2019;Wheelahan, 2007Wheelahan, , 2015. The intended curricula for Swedish demands-based and employer-driven HVE do not include knowledge that supports the kind of influence in conversations or controversies that is necessary for full democratic inclusion and participation in civic practice.…”
Section: Decentralised Organisation Of Education and Knowledgementioning
confidence: 99%
“…Time and pace were outside the students' control, and the activities fostered a collective identity (cf. Nylund et al 2019). In one of the classes, the boys in the class were not high-performing, and a group of five to seven of the girls both performed better than the rest of the class in the kitchen and (interestingly) performed 'personal' activities in school.…”
Section: Acting Femininities In Gendered Vetmentioning
confidence: 94%
“…Thirdly, subjectification and socialization were emphasized in the participants' narratives. Quite the opposite has been raised in earlier studies [28,52], as qualification has often been appraised as one of the major functions of VET, which means preparing students with skills appropriate for both the world of work and for citizenship. It seems that schools are emphasizing academic and vocational achievement instead of developing students' competencies to manage their careers [42,43,47,48], whereas students with special educational needs emphasize their personal subjective growth.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have also indicated that schools are mostly helping their students in their academic achievement and not in developing competencies to manage their own careers [42,43,47,48]. Furthermore, previous research has tended to focus on the VET teachers' position in VET and correspondingly on pedagogical practices [49][50][51][52][53].…”
Section: Special Needs Students At the Center Of The Studymentioning
confidence: 99%